Optimalisasi Peran Generasi Muda Dalam Peningkatan Kesadaran Digital Masyarakat Kelurahan Sawah Lebar Rt 12 Meranti Iv - Haikal, Franky; Nengsi, Ervina Ayu; Astuti, Esti Puji; Ramadhanni, Mutiara; Dita, Jaga; Mahdalena, Desi (Jurnal Dehasen Untuk Negeri, 2026)
This community service activity was carried out in Sawah Lebar Subdistrict as an effort to improve digital literacy, particularly in RT 12 of Meranti IV Street. The main problem faced by the community is the low understanding of digital technology, information security, and the use of digital tools to support daily activities. The proposed solution consists of digital literacy workshops and training for students, youth, and residents. This service program was conducted through several stages: situation analysis, program planning, implementation, and evaluation. The results indicate an increase in participants’ understanding of digital literacy concepts, digital ethics, and basic skills in using digital devices. This program has contributed positively to raising awareness of the importance of digital literacy as part of technological adaptation.